Junior High School Students’ Understanding of The Nature of Science - Habiby, Iqbal; Hernani, Hernani; Suwandi, Tri (FKIP Universitas Lampung, 2020)
Junior high school students’ understanding of the nature of science. Objective: The purpose of this research is to explore the junior high school students’ understanding of nature of science (NOS). Methods: The survey in this research was conducted in 8th grade as many as 80 students from three schools in East Prabumulih Sub-District, South Sumatera Province, Indonesia, which was determined by stratified random sampling technique. Students’ understanding of 7 aspects of NOS was measured using a questionnaire containing 35 items consisting of 4 Likert scale statements (scale 1-5) and 1 question open-ended responses to each aspect of NOS. Findings: The results showed that students’ understanding of NOS is still inadequate. The students’ understanding of NOS that inadequate shown through by the small percentage of the informed view category on all aspects of the NOS measured, both Likert scale items and open-ended responses. Conclusion: These findings emphasize the need for learning to improve understanding of NOS for students.Keywords: nature of science, survey method, students understanding.DOI: 10.23960/jpp.v10.i2.202001